Numerical Analysis of the Mechanical Behavior of Lightweight Metal‐CFRP Joints1. Issue 9 (29th April 2013) - Konchakova, Natalia; Balle, Frank; Müller, Ralf; Steinmann, Paul; Eifler, Dietmar; Barth, Franz Josef
<x xml:space="preserve">Abstract</x> Influence of the welding geometry on the mechanical characteristics of light metal/carbon fiber reinforced polymer overlapped structures is analyzed. An elastoplastic model with Lemaitre‐type damage is used for the simulation of the mechanical behavior of the interface material. An interfacial traction–separation law is applied. Finite element method is used for the simulation of force–displacement curves of ultrasonically welded AA5754/CF‐PA66 joints. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>